The impact of shared reading on the fluency of struggling ESL readers in grade three / Tay Tiew Sui - Tay, Tiew Sui (2014)
The main purpose of this action research is to explore the impact of shared reading on struggling Grade Three English as a Second Language (ESL) readers, aged 8-9, in a Malay- medium primary school in urban Kuala Lumpur. Its secondary purpose is to find out if the subjects enjoy shared reading with big books and their expectations in the reading classroom. Instrumentation consists of audio recordings of unpractised and practised texts, video recordings of shared reading lessons in session, and a questionnaire to collect feedback. 12 subjects out of 60 were identified as struggling readers. These subjects participated in whole class shared reading sessions and in their own group shared reading sessions. The audio recordings of each subject were analysed for number of words correct per minute (WCPM) for unpractised texts before shared reading sessions and practised texts after shared reading sessions. Findings indicated that the fluency (WCPM) of the subjects increases after treatment. 94 % of the respondents of the questionnaire indicated that they enjoyed shared reading with big books and expected the teacher to be their role model during reading lessons. I come to the conclusion that shared reading has a positive impact on both struggling and proficient ESL readers.